An Effective Translation: The Development of Hyaluronan-Based Medical Products From the Physicochemical, and Preclinical Aspects - Huerta-Ángeles, Gloria; Nešporová, Kristina; Ambrožová, Gabriela; Kubala, Lukas; Velebný, Vladimir (Frontiers in Bioengineering and Biotechnology, 2018)
This review shows the steps towards material selection focalized on the design and development of medical devices based on hyaluronan (HA). The selection is based on chemical and mechanical properties, biocompatibility, sterilization, safety and scale-up costs. These facts play a vital role in the industrialization process. Approved medical devices containing-HA are illustrated to identify key parameters. The first part of this work involves the steps towards a complete characterization of chemical and mechanical aspects, reproducibility of the processes and scale up. In a second stage, we aimed to describe the preclinical in vitro and in vivo assays and selected examples of clinical trials. Furthermore, it is important to keep in mind the regulatory affairs during the research and development (R&D) using standardization (ISO standards) to achieve the main goal, which is the functionality and safety of the final device. To keep reproducible experimental data to prepare an efficient master file for the device, based on quality and recorded manufacturing data, and a rigorous R&D process may help towards clinical translation. A strong debate is still going on because the denominated basic research in HA field does not pay attention to the purity and quality of the raw materials used during the development. So that, to achieve the next generation of devices is needed to overcome the limitations of state of art in terms of efficacy, biodegradability, and non-toxicity.